The Mediating Role of the World Trade Organisation (WTO) Director General (DG) in Multilateral Trade Negotiations : the Case Study of the July 2008 WTO Ministerial Meeting - Qobo, Mzukisi (University of Pretoria, 2015)
Mini-dissertation (MDIPS)--University of Pretoria, 2014.